Pengaruh Current Ratio dan Inventory Turnover terhadap Return On Asset pada PT Kimia Farma Tbk - Suraya, Amthy; Astuti, Eni Puji; Yasin Fadli, Achmad Agus (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
The purpose of this research is to analyze the Effect of Current Ratio and Inventory Turnover on Return On Assets of PT Kimia Farma Tbk. The sample used in this study is purposive sampling. The method used in this study is a descriptive method with a quantitative approach. The data used are secondary data in the form of financial statements of PT Kimia Farma Tbk for the period 2018-2024. Data analysis used is the Classical Assumption Test, Regression Analysis, Determination Coefficient, T Test and F Test. The results of the study indicate that partially there is a significant effect of Current Ratio on Return On Assets with a Tcount value of 5.763> Ttable 2.776 with a significance value of 0.004<0.05. And Inventory Turnover partially has no effect on Return On Assets where the Tcount value is -0.841<Ttable 2.776 with a significance value of 0.448>0.05. Simultaneously, Current Ratio and Inventory Turnover have a significant effect on Return on Asset F count 49.646>F table 5.79 with a significance value of 0.001<0.05